Plan de marketing para la empresa Merquiauto S. A en el cantón Quevedo año 2015 - Cox Intriago, Sullin Ailin (2016)
Merquiauto SA is a local company with several years in the market of Canton Quevedo But due to increased competition affected and the absence of a marketing plan, sales have decreased significantly by 60% in the past two years, because there is no market positioning and remembrance of the company in the minds of consumers due to the null advertising and promotions. They have not established short- and long-term and do not have marketing strategies, development and growth. For the present work, a market research was conducted to 379 people considering the layers A, B and C + in the city of Quevedo, because this population has the economic means to purchase a vehicle through market research the situation was determined enterprise and research results highlighted the need to develop advertising for the company to become known in the market and create design strategies and action plans, which allow to increase sales and position in the market Merquiauto Quevedo Canton. Analysis BCG matrix (Boston Consulting Group Matrix) where the market share of competing vehicles in the Quevedo canton where Merquiauto question is located in the matrix was shown was performed. Therefore it was concluded that the company has high growth and low market share must evaluate the strategy in this area, which eventually can become a star or a dog, the internal and external study of the company we unveiled the SWOT (Strengths, Weaknesses, Opportunities and Threats) where his strength is the variety of vehicles on different brands, one of the greatest threats to the company's rising tariffs that the country is going in one way or another way affect marketing. Budget marketing plan which will invest $ 34.936.00 with the implementation of the marketing plan the company can meet the objectives and desired best results for increasing sales and positioning.